2010
DOI: 10.1002/prop.201000067
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino physics beyond neutrino masses

Abstract: We briefly summarise the current status of neutrino masses and mixing, paying special attention to the prospects for observing new leptonic interactions.Comment: Latex 6 pages. To appear in the proceedings of 9th Hellenic School and Workshops on Elementary Particle Physics and Gravity (CORFU2009), Corfu, Greece, August 30-September 20, 2009

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…What about production of low scale seesaw messengers at colliders? A recent review on the situation can be found in 103 . While Majorana neutrino production proves difficult because of the constraint of its small mixing with SM particles, Higgs and fermion triplets have gauge quantum numbers and can be observed up to TeV masses.…”
Section: Neutrino Mass and Mixing: Theoretical Originmentioning
confidence: 99%
See 1 more Smart Citation
“…What about production of low scale seesaw messengers at colliders? A recent review on the situation can be found in 103 . While Majorana neutrino production proves difficult because of the constraint of its small mixing with SM particles, Higgs and fermion triplets have gauge quantum numbers and can be observed up to TeV masses.…”
Section: Neutrino Mass and Mixing: Theoretical Originmentioning
confidence: 99%
“…We have mentioned already high energy tests of lepton number violation such as the like-sign dilepton signature of heavy Majorana neutrino production 103,212 , Higgs triplet decays 209 , or resonant selectron production 237 . One may wonder whether there are low energy processes, in analogy to 0νββ, which can probe the effective Majorana mass, maybe even without any nuclear physics complications.…”
Section: Alternative Processes To Neutrino-less Double Beta Decaymentioning
confidence: 99%
“…1. However, if we allow for light RH neutrinos and new fourfermion interactions of the electroweak size up to a factor of a few, and possible model dependent cancellations, present experimental constraints leave room for light RH neutrinos observable at a neutrino factory, and new mediators observable at LHC [4,7]. Indeed, although limits on new physics described by dimension six operators are typically of the order of 1-10 % [8], if we allow for cancellations some deviations from the SM can be larger.…”
Section: Observable Rh Neutrino Productionmentioning
confidence: 99%
“…The discovery of a non-zero 13 angle [51][52][53][54] lead to a broadening to (product) groups beyond the early 4 , 4 , or (double tetrahedral) , and to considering spontaneous breaking of such symmetries. Interestingly, models with flavor symmetries often feature a suppression of the Yukawa couplings in the composite sector (inducing lepton masses after mixing), since those control the breaking of (see, e.g., [20]). Moreover, left-handed (LH) lepton compositeness is bound to be small due to lack of custodial It would be interesting to examine the emergence of a hierarchical spectrum explicitly in a setup of MFPC.…”
Section: Partial Compositeness: Effective Description and Different E...mentioning
confidence: 99%
“…Employing such triplets, a unification of the right-handed (RH) lepton sector is possible and a single, symmetric, representation of SO( 5) can host both the charged RH leptonic SU(2) singlet and the RH seesaw triplet [32,34,35]. This leads to a more minimal model for leptons, featuring less new particles and less parameters, than conventional analogues to minimal viable (MCHM 5 -like) quark sectors, which require in fact mixings with four fundamental 5's of SO (5) [4,20].…”
Section: Minimal Seesaw Model and Composite Leptonsmentioning
confidence: 99%